Tuberculin Skin Test Negativity Is Under Tight Genetic Control of Chromosomal Region 11p14-15 in Settings With Different Tuberculosis Endemicities - Cobat, Aurélie; Poirier, Christine; Hoal, Eileen; Boland-Auge, Anne; de La Rocque, France; Corrard, François; Grange, Ghislain; Migaud, Mélanie; Bustamante, Jacinta; Boisson-Dupuis, Stéphanie; Casanova, Jean-Laurent; Schurr, Erwin; et al. (The Journal of infectious diseases, 2015)
A substantial proportion of subjects exposed to a contagious tuberculosis case display lack of tuberculin skin test (TST) reactivity. We previously mapped a major locus (TST1) controlling lack of TST reactivity in families from an area in South Africa where tuberculosis is hyperendemic. Here, we conducted a household tuberculosis contact study in a French area where the endemicity of tuberculosis is low. A genomewide analysis of TST negativity identified a significant linkage signal (P < 3 × 10⁻⁵) in close vicinity of TST1. Combined analysis of the 2 samples increased evidence of linkage (P = 2.4 × 10⁻⁶), further implicating genetic factors located on 11pl4-15. This region overlaps the TNF1 locus controlling mycobacteria-driven tumor necrosis factor α production.